WEBINAR SEBAGAI MEDIA BIMBINGAN KLASIKAL SEKOLAH UNTUK PENDIDIKAN SEKSUAL BERBASIS ONLINE (Meta Analisis Pedagogi Online) - Anaway Irianti Mansyur; Rif’ah Purnamasari; RA Murti Kusuma (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2019)
Technological sophistication presents new ideas in the world of education. Webinars is one of the solutions to various existing researches about the effectiveness of using webinar media as online pendagogy. The era of big data, iGeneration leads to all activities based online. Technology collaboration with education is integrated into online learning about sexual education in adolescents at school. Classical guidance for sexual education really needs to be conveyed with interesting methods tailored to the existing generation, namely generation Z (internet generation). This study will be discussed with a literature review of various relevant studies that have ever existed.